Public Health Management a Curative Tool for the Public Health Related Problems - Bali, Surya (Indian Journal of Community Health, 2022)
Health always remains a core component in the life of human beings and considered as a major instrument of overall socio-economic development. Concept of health has been defined and understood in different ways by different cultures. The two major division of medicine namely curative and preventive medicine came into light at the close of 19th century. Although origin of Medicine and Public health goes back to ancient Greek mythology, Asclepius was the Greek god of Healing. He was the son of Apollo and the Coronis. Asclepius was married to Epione, with whom he had five daughters: Hygieia, Panacea, Aceso, Iaso, and Aglaea. Hygieia was the goddess of health, cleanliness and hygiene. Follower of panacea practiced curative medicine and were called healer and followers of Hygieia were called as Hygienist or Public Health experts (1). Concept of Public Health came from this hygienist category of healthcare personals. The Constitution of the World Health Organization, which came into force on April 7, 1948, defines health “as a state of complete physical, mental and social well-being.”(2) In today’s world more emphasis is given on physical health and most of the resources are diverted for the care of physical health especially for the medical treatment. Other domains of health care remain neglected. Public health applies to the holistic approach for the care of health. Physical health is best taken care by the judicious mix of public health and medical domain of health. The evolution of concepts of public health tries to address new challenges of population health like non communicable diseases, cancers, accidents, injuries, inequities, increasing cost of care, poor quality of care, and poor patient satisfaction etc.